Peran BPBD dalam Pemberdayaan Penanganan Banjir Bandang di Kelurahan Lodoyong, Ambarawa, Semarang - Saipullah Hasan; Riyadi Riyadi; Yayuk Rukayah; Avin Wimar Budyastomo; Winda Sari (UIN Siber Syekh Nurjati Cirebon, 2022)
The Lodoyong Village area is an area that is prone to flooding. Therefore, handling is needed to protect the community from the threat of disaster. This study aims to determine the role of BPBD Semarang in empowering banjir bandang management in Lodoyong Village, Ambarawa District, Semarang Regency. The research method uses descriptive qualitative. The method of data collection using observation and interviews. Observations were carried out by observing directly at the location affected by the flood disaster. Meanwhile, interviews were conducted with BPBD Semarang and affected communities. The results showed that the role of BPBD in disaster management was carried out at the pre-disaster stage by establishing community preparedness and post-flood evacuation, logistical assistance and repair of public infrastructure. These various actions were taken to build community capacity in restoring socio-economic conditions